DOMINO CLINICAL CARDS TRAINING TO IMPROVE LECTURERS' ABILITIES IN CLINICAL REASONING LEARNING MEDIA - Irfannuddin Irfannuddin; Eka Febri Zulissetiana; Susilawati Susilawati; Mailan Alexander (Conferences of Medical Sciences Dies Natalis, 2021)
Medical practitioners sometimes perform inappropriate decisions and procedures. In making decisions, doctors may take a poor thinking called cognitive and representative bias.One matrix approach that can be developed to build learners' clinical reasoning is the domino game method. Domino card games (DCC) are a form of visual learning that can increase student learning motivation. DCC media is carried out in the form of competitive games. However, DCC is part of collaborative and peer learning methods. Collaborative learning is a method in which learners collaborate with each other. This method is considered to increase learning motivation. Collaboration makes them understand their learning process. The process of collaboration makes them internalize knowledge with critical thinking skills. Peer learning is the learning activity of a group of students from a similar social group. Peer learning activities can be in peer tutoring, peer assessment, or game and simulation forms. Peer learning tutoring can improve the quality of learning efficiently.DCC is an alternative instrument that can be developed to improve clinical reasoning skills. Through this training, some lecturers have been able to compile and develop DCC prototypes. Furthermore, they can apply according to their respective fields of knowledge.